(untitled) (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
ABSTRACT This study addresses the failure of existing discipleship models to sustain active participation and faith retention among urban students in Tangerang, Indonesia, where high academic pressure, social fragmentation, and secularization undermine individualistic approaches. Employing a Systematic Literature Review (SLR) method, the research synthesizes findings from theology, community sociology, and adolescent psychology to identify key themes and critique current models. The main results reveal three critical gaps: theoretical (Western-centric discipleship and sense of community frameworks ignore Asian collectivist and hierarchical contexts), empirical (no systematic study on community-based discipleship for Indonesian students), and methodological (fragmented qualitative studies lacking rigorous synthesis). The novelty lies in proposing the Community-Based Discipleship Framework for Urban Youth (CBD-UY), which integrates McMillan and Chavis’s sense of community, Lickona’s character formation, and Gotham’s urban context theory. Unlike existing models, CBD-UY positions community as a safe “third space” for identity exploration and spiritual resilience, with leaders as facilitators rather than sole authorities. This framework contributes a contextualized, testable alternative for urban youth discipleship in Indonesia, addressing the need for holistic, relational approaches beyond doctrinal transfer. Keywords: community-based discipleship; urban youth; faith retention; Indonesia; Systematic Literature Review ABSTRAK Penelitian ini menyoroti kegagalan model pemuridan yang ada dalam mempertahankan partisipasi aktif dan retensi iman pelajar urban di Tangerang, Indonesia, di mana tekanan akademik tinggi, fragmentasi sosial, dan sekularisasi melemahkan pendekatan individualistik. Menggunakan metode Systematic Literature Review (SLR), penelitian ini mensintesis temuan dari teologi praktika, sosiologi komunitas, dan psikologi perkembangan remaja untuk mengidentifikasi tema-tema kunci dan mengkritisi model yang ada. Hasil utama mengungkap tiga celah kritis: teoretis (kerangka pemuridan dan sense of community yang berpusat pada Barat mengabaikan konteks Asia yang kolektivistik dan hierarkis), empiris (belum ada studi sistematis tentang pemuridan berbasis komunitas untuk pelajar Indonesia), dan metodologis (studi kualitatif fragmentaris tanpa sintesis ketat). Kebaruan terletak pada pengusulan Community-Based Discipleship Framework for Urban Youth (CBD-UY), yang mengintegrasikan teori sense of community dari McMillan dan Chavis, pembentukan karakter dari Lickona, dan konteks urban dari Gotham. Berbeda dengan model yang ada, CBD-UY memosisikan komunitas sebagai “ruang ketiga” yang aman untuk eksplorasi identitas dan ketahanan spiritual, dengan pemimpin sebagai fasilitator, bukan otoritas tunggal. Kerangka ini memberikan alternatif kontekstual yang teruji untuk pemuridan pelajar urban di Indonesia, menjawab kebutuhan pendekatan holistik dan relasional di luar transfer doktrinal. Kata kunci: pemuridan berbasis komunitas; pelajar urban; retensi iman; Indonesia; Systematic Literature Review